2001
DOI: 10.1074/jbc.m101940200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Amino Acids of Escherichia coli DnaC Protein in an N-terminal Domain Interact with DnaB Helicase

Abstract: Escherichia coli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 48 publications
6
65
1
Order By: Relevance
“…DnaC protein is another major component of E. coli chromosomal DNA replication (15,17). This replication factor is required for assisting DnaB to bind to the replication origin and appears to have a pivotal role in initiation of helicase function (50,51).…”
Section: Analysis Of In Vitro Primer Synthesis In the Presence Of Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…DnaC protein is another major component of E. coli chromosomal DNA replication (15,17). This replication factor is required for assisting DnaB to bind to the replication origin and appears to have a pivotal role in initiation of helicase function (50,51).…”
Section: Analysis Of In Vitro Primer Synthesis In the Presence Of Dnamentioning
confidence: 99%
“…Binding of DnaB to singlestranded DNA (ssDNA) 1 is controlled by its interaction with DnaC. Association with DnaB stimulates the DNA binding activity of DnaC, and with the help of DnaA, it loads DnaB on the ssDNA (15)(16)(17). In the next step, primase, the DnaG gene product and a single-stranded DNA-dependent RNA polymerase, is recruited to the replication fork through a transient protein-protein interaction with DnaB.…”
mentioning
confidence: 99%
“…Because amino acid substitutions within residues 10-44 near the amino terminus of DnaC impair the interaction between DnaC and DnaB, this region of DnaC apparently binds directly to DnaB to form the DnaB -DnaC complex (Ludlam et al 2001). Initial studies showed that six DnaC monomers bind per DnaB hexamer (Wickner and Hurwitz 1975;Kobori and Kornberg 1982;Lanka and Schuster 1983).…”
Section: Dnaa Is the Replication Initiator In Bacteriamentioning
confidence: 99%
“…The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health. 4 The abbreviations used are: ssDNA, single-stranded DNA; SSB, ssDNA-binding protein; SSB-Ct, SSB C terminus; ITC, isothermal titration calorimetry. …”
mentioning
confidence: 99%